The hyperlicious function is defined as

  • \(h_x(a,b) = \text{hyper}(a,x + 2,b)\),
  • \(h_x(a,b,c,\ldots,m,n,1) = h_x(a,b,c,\ldots,n)\), and
  • \(h_x(a,b,c,\ldots,m,n) = h_{h_x(a,b,c,\ldots,m - 1)}(a,b,c,\ldots,m)\).[1]


\(h_3(2,6) = \text{hyper}(2,5,6) = 2 \uparrow^5 6\)

\(h_4(2,6,2) = h_{h_4(2,5)}(2,6) = h_{\text{hyper}(2,6,5)}(2,6) = 2 \uparrow^{2 \uparrow^{6} 5+2} 6\)

Growth rateEdit

\(h(x) = h_x(x,x...x,x)\) with x x's in the array is approximately \(f_{\omega+1}(x)\)

Sources Edit

  1. A googol is a tiny dot

See also Edit

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.